Amidomagnesium cations. Issue 21 (26th February 2019) - Banerjee, Sumanta; Ankur,; Andrews, Alex P.; Varghese, Babu; Venugopal, Ajay
Abstract : We report the synthesis, structure and reactivity of molecular amidomagnesium cations bearing tris{2-(dimethylamino)-ethyl}amine (Me6 TREN). Abstract : We report the synthesis, structure and reactivity of molecular amidomagnesium cations bearing tris{2-(dimethylamino)-ethyl}amine (Me6 TREN). Me6 TREN binds to the cationic magnesium centre exhibiting κ 4 and κ 3 coordination modes in [Me6 TREN-Mg-N(SiHMe2 )2 ] + and [Me6 TREN-Mg-N(SiMe3 )2 ] + respectively. [Me6 TREN-Mg-N(SiHMe2 )2 ] + reacts with benzophenone resulting in the insertion of the carbonyl group across β-SiH bond. The reaction between [Me6 TREN-Mg-N(SiMe3 )2 ] + and CO2 leads to [Me6 TREN-Mg-OSiMe3 ] +, while the reaction with H2 O results in [Me6 TREN-Mg-OH]2 2+ . Attempts to prepare hydridomagnesium cations from [Me6 TREN-Mg-N(SiMe3 )2 ] + using KH resulted in the precipitation of MgH2 and the isolation of [(Me6 TREN)K(THF)3 ] + .